“Ruslani” Social Innovation in Public Service Based on Community Empowerment in Samarinda Seberang Sub-District of Samarinda City (Jurnal Bina Praja, 2018)
The number of complaints, the slow performance, and the lack of productivity demands the need for a reformed public sector. Reform can be done with social innovation by involving and making citizens as participants and end users. Not only that, fundamentally, changing the role of various stakeholders in the provision of services. Where citizens act to decide themselves and play an active role in making decisions. “Ruslani” Innovation is one of the forms of social innovations based on the problem of limited access to the fulfillment of healthy habitable home ownership for the poor. How the implementation of Ruslani innovation based on the community empowerment done in Samarinda Seberang Sub-District is analyzed in this research. By using a descriptive qualitative method, data collection is conducted through in-depth interviews of key informants selected purposively and by analyzing secondary data documents. The results show that the implementation of Ruslani program has been aligned based on the principle of Law Number 23 of 2014 on Regional Government, according to principles; increased efficiency; improvement of effectiveness; improvement of service quality; no conflict of interest; oriented to the public interest; done openly; fulfill propriety values; can be accounted for the results that are not for self-interest. On the other hand, the Ruslani program has also followed the criteria; relative advantage, compatibility, complexity, trialability, observability, and criteria of service innovation based on the Regulation of Menpan-RB Number 19 of 2016, which in its implementation has introduced a new, productive, impactful and beneficial approach, and the most important thing is this program has running sustainably. Factors supporting and inhibiting innovation based on environmental categories, organizations, and individuals generally do not hinder the implementation of the program.